Indian Financial Services Sector: Emerging Marketing Challenges and Strategies - Surayya, Teki (Indian Journal of Marketing, 2005)
Indian economy has undergone a sea change in its structure, policy and regulation, due to liberalization and globalization, since 1991. Markets for services are no exception this. The contribution of services sector (including sizable contribution from financial services sector) for GDP has increased to 51% in 2003, from 36% in 1980. The financial services sector includes factoring, merchant banking, venture capital etc. The paper aims at a couple objectives (1) to analyze the contribution of service sector in general and financial service sector in particular to India’s GDP, (2) to outline the emerging marketing challenges/problems and strategies for Indian financial service sector in the current post-liberalized era.